The Impact of ACE2 Polymorphisms on COVID-19 Disease: Susceptibility, Severity, and Therapy - Chen, Fei; Zhang, Yankun; Li, Xiaoyun; Li, Wen; Liu, Xuan; Xue, Xinyu (Frontiers in Cellular and Infection Microbiology, 2021)
The coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has currently spread worldwide, leading to high morbidity and mortality. As the putative receptor of SARS-CoV-2, angiotensin-converting enzyme 2 (ACE2) is widely distributed in various tissues and organs of the human body. Simultaneously, ACE2 acts as the physiological counterbalance of ACE providing homeostatic regulation of circulating angiotensin II levels. Given that some ACE2 variants are known to cause an increase in the ligand-receptor affinity, their roles in acquisition, progression and severity of COVID-19 disease have aroused widespread concerns. Therefore, we summarized the latest literature and explored how ACE2 variants and epigenetic factors influence an individual’s susceptibility to SARS-CoV-2 infection and disease outcome in aspects of ethnicity, gender and age. Meanwhile, the possible mechanisms for these phenomena were discussed. Notably, recombinant human ACE2 and ACE2-derived peptides may have special benefits for combating SARS-CoV-2 variants and further studies are warranted to confirm their effects in later stages of the disease process. As the uncertainty regarding the severity and transmissibility of disease rises, a more in-depth understanding of the host genetics and functional characteristics of ACE2 variants will not only help explain individual clinical differences of the disease, but also contribute to providing effective measures to develop solutions and manage future outbreaks of SARS-CoV-2.